Investigation of the ¹⁶O(γ, ρ)³H3α reaction at the energies below the meson production threshold - Afanasiev, S.N. (Вопросы атомной науки и техники, 2021)
The reaction ¹⁶O(γ, ρ)³H3α induced by bremsstrahlung photons of endpoint energy Emaxγ = 150 MeV has been studied by the method of a diffusion chamber in a magnetic field. The energy dependence of the total cross section has been measured in the energy range from the threshold and has been founded a broad resonance centered at 55 MeV. The rate of decrease in the cross section undergoes a change in the region around 55 MeV. A comparison was made with the cross section for reactions ⁴He(γ, p)³H and ¹²С(γ, р)³H2α. The agreement between the shapes of distributions for the (γ, p)³H reactions is evident and was concluded that the mechanism of interaction of the γ-quantum with the nucleus is similar. The dependence of average kinetic energy of particles on the total kinetic energy was determined. In the whole energy interval, the distribution for a proton is more than the statistical distribution. Distribution of relative energy of the proton and ³H nucleus in their c.m.s. does not agree with the predictions of the mechanism of photon absorption by an α-particle cluster, but at energies above the maximum, it agrees with calculations within the framework of the quasi-deuteron model of photoabsorption. Виконано аналіз подій реакції ¹⁶O(γ, ρ)³H3α, отриманих методом дифузійної камери в магнітному полі на пучці гальмівних фотонів з Eγmax = 150 МеВ. В енергетичній залежності реакції виявлено широкий максимум при Eγ ∼ 55 МеВ. Вище максимуму спостерігається зміна швидкості убування залежності. Виконано порівняння з виходами реакцій ⁴He(γ, p)³H і ¹²С(γ, р)³H2α, і зроблено висновок про подібність механізму взаємодії γ-кванта з ядром. Основну частину енергії забирає протон, причому при Eγ > 55 МеВ відбувається різка зміна залежності відносного вкладу частинок у повну енергію системи T₀. Поведінка залежності розподілу відносної енергії пари p+³H від T₀ не узгоджується з розрахунками в рамках α-кластерного механізму взаємодії γ-кванта з ядром, але при енергії вище максимуму узгоджується з розрахунками в рамках квазідейтронної моделі фотопоглинання. Выполнен анализ событий реакции ¹⁶O(γ, ρ)³H3α, полученных методом диффузионной камеры в магнитном поле на пучке тормозных фотонов с Eγmax = 150 МэВ. В энергетической зависимости реакции обнаружен широкий максимум при Eγ ∼ 55 МэВ. Выше максимума наблюдается изменение скорости убывания зависимости. Выполнено сравнение с выходами реакций ⁴He(γ, p)³H и ¹²С(γ, р)³H2α, и сделан вывод о подобии механизма взаимодействия γ-кванта с ядром. Основную часть энергии уносит протон, причем при Eγ > 55 МэВ происходит скачкообразное изменение зависимости относительного вклада частиц в полную энергию системы T₀. Поведение зависимости распределения относительной энергии пары p+³H от T₀ не согласуется с расчетами в рамках α-кластерного механизма взаимодействия γ-кванта с ядром, но при энергии выше максимума согласуется с расчетами в рамках квазидейтронной модели фотопоглощения.